1990
DOI: 10.1038/343457a0
|View full text |Cite
|
Sign up to set email alerts
|

The preS2/S region of integrated hepatitis B virus DNA encodes a transcriptional transactivator

Abstract: Hepatitis B virus (HBV) is regarded as the main aetiologic factor in the development of human hepatocellular carcinoma (HCC), one of the most frequent fatal malignancies worldwide. Detection of integrated HBV sequences in the cellular DNA of almost all HCCs studied, and the recent finding that the integrated HBV open reading frame (orf) X encodes a transactivating activity, supports the notion that integrated HBV DNA could contribute to liver carcinogenesis by activation of cellular genes in trans. But not all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
126
0
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(138 citation statements)
references
References 30 publications
9
126
0
3
Order By: Relevance
“…Previously, a transcription activation activity was ascribed to truncated forms of M protein (MHBs t ) (57). It might be speculated that the autoregulatory function of M protein uncovered in the present study is the same as that of MHBs t described previously.…”
Section: Protein Regulates Surface Gene Expression By Interacting Wsupporting
confidence: 67%
See 1 more Smart Citation
“…Previously, a transcription activation activity was ascribed to truncated forms of M protein (MHBs t ) (57). It might be speculated that the autoregulatory function of M protein uncovered in the present study is the same as that of MHBs t described previously.…”
Section: Protein Regulates Surface Gene Expression By Interacting Wsupporting
confidence: 67%
“…Upon close examination, however, these two are quite different. First, the transcription transactivator function of MHBs t was originally based on its ability to transactivate the SV40 promoter-reporter gene (57). Later, it was found that it may indirectly transactivate reporter genes containing transcription factor-binding sites, e.g.…”
Section: Protein Regulates Surface Gene Expression By Interacting Wmentioning
confidence: 99%
“…Such a mutant is capable of transactivating several promoters including those of oncogenic proteins. [32][33][34] The truncation point in the A529T mutant, however, was located just at the border of the defined ''transactivity-ON-region.'' 34 Clinically, none of the patients harboring this mutant developed hepatocellular carcinoma to date.…”
mentioning
confidence: 99%
“…To compare the mRNA expression in various organs of these mice, we performed both RT-PCR analysis and ribonuclease protection assay (RPA) [6]. Antisense RNA probe labeled with 33 P-CTP was generated as a transcript RNA [7,9].…”
mentioning
confidence: 99%